2021
DOI: 10.3390/cancers14010194
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage and Neutrophil Interactions in the Pancreatic Tumor Microenvironment Drive the Pathogenesis of Pancreatic Cancer

Abstract: Despite modest improvements in survival in recent years, pancreatic adenocarcinoma remains a deadly disease with a 5-year survival rate of only 9%. These poor outcomes are driven by failure of early detection, treatment resistance, and propensity for early metastatic spread. Uncovering innovative therapeutic modalities to target the resistance mechanisms that make pancreatic cancer largely incurable are urgently needed. In this review, we discuss the immune composition of pancreatic tumors, including the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 232 publications
(348 reference statements)
0
32
0
Order By: Relevance
“…At the early stage of zebrafish larvae development, macrophages and neutrophils are two major populations in the innate immune system. Both macrophages and neutrophils have been shown to regulate anti-tumor immunity and immune evasion [ 9 ]. In our research, PANC1 and BxPC3 recruited more coro1a: GFP + innate immune cells to the TME compared to AsPC1 cells, and the co-localization of coro1a: GFP + cells with the tumor cells was increased from 1 dpi to 4 dpi by three-fold for PANC1 and BxPC3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the early stage of zebrafish larvae development, macrophages and neutrophils are two major populations in the innate immune system. Both macrophages and neutrophils have been shown to regulate anti-tumor immunity and immune evasion [ 9 ]. In our research, PANC1 and BxPC3 recruited more coro1a: GFP + innate immune cells to the TME compared to AsPC1 cells, and the co-localization of coro1a: GFP + cells with the tumor cells was increased from 1 dpi to 4 dpi by three-fold for PANC1 and BxPC3.…”
Section: Discussionmentioning
confidence: 99%
“…However, tumor cells also develop mechanisms to evade immune surveillance and could mold myeloid cells to serve the tumor. Functionally, tumor-associated myeloid cells are often divided into anti- or pro-tumor subgroups [ 9 , 10 , 11 ]. The anti-tumoral group are associated with immunostimulatory cells with the secretion of pro-inflammatory cytokines (e.g TNF-α, IL-12, and IL-6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophils are thought to be recruited to the pancreatic tumors by chemokines and other signaling molecules released from tumor cells. 8 But how do neutrophils accumulate in non-tumor organs? Studies have shown that tumor-derived factors released from primary tumor site could systemically condition distant sites for potential metastases.…”
mentioning
confidence: 99%